2013
DOI: 10.1248/cpb.c13-00160
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Flowers. XXXX.<sup>1)</sup> Structures of Dihydroisocoumarin Glycosides and Inhibitory Effects on Aldose Reducatase from the Flowers of <i>Hydrangea macrophylla</i> var. <i>thunbergii</i>

Abstract: Key words florahydroside; Hydrangea macrophylla var. thunbergii; medicinal flower; dihydroisocoumarin glycoside; aldose reductase; acylated quinic acid analogThe Saxifragaceae plant, Hydrangea (H.) macrophylla Seringe var. thunbergii Makino, is native to Japan. The processed leaves of this plant (Hydrangea Dulcis Folium) are currently used as a natural medicine for an oral refrigerant and as a sweetener for diabetic patients. In addition, these preparations are listed in the Japanese Pharmacopoeia. Previously,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Although belonging to the dihydroisocoumarin, the biological activity of HMIO has rarely been reported. It has been reported that dihydroisocoumarins show very important bioactivities, such as selective inhibition of aromatase (Endringer et al ., ), anticancer activity (Higgins et al ., ) and inhibitory effects on aldose reducatase (Liu et al ., ). It is probable that HMIO also plays an important role for the pharmacological effects of STM in vivo .…”
Section: Resultsmentioning
confidence: 97%
“…Although belonging to the dihydroisocoumarin, the biological activity of HMIO has rarely been reported. It has been reported that dihydroisocoumarins show very important bioactivities, such as selective inhibition of aromatase (Endringer et al ., ), anticancer activity (Higgins et al ., ) and inhibitory effects on aldose reducatase (Liu et al ., ). It is probable that HMIO also plays an important role for the pharmacological effects of STM in vivo .…”
Section: Resultsmentioning
confidence: 97%
“…Although it belongs to the dihydroisocoumarins, the biological activity of ECR is rarely reported. It has been reported that dihydroisocoumarins show very important bioactivities, such as selective inhibition of aromatase (Denise et al, 2008), anticancer (Higgins et al, 2009) and inhibitory effects on aldose reductase (Liu et al, 2013). It is probable that ECR also plays an important role in the pharmacological effects of STM in vivo.…”
Section: Quantification Of Ecr In Rat Plasmamentioning
confidence: 99%
“…Caffeoylquinic acid analog, 4,5-Di- O -trans-caffeoyl- d -quinic acid isolated from Hydrangea macrophylla var. thunbergii (bigleaf hydrangea) and Ilex paraguariensis (Yerba mate) showed the strongest inhibitory activity against RLAR at IC 50 value of 0.29 µM [ 55 ]. Inhibitory effect of quinic acid with two caffeoyl groups assisted the potency.…”
Section: Resultsmentioning
confidence: 99%